Pengaruh Dukungan Sosial Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha - Rico Septia B. (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The greater the convenience offered, the support and facilities that have been prepared, it is hoped that many people will be motivated to build businesses, especially the millennial generation. Of course, every individual will have an interest in entrepreneurship based on different causal factors. Therefore, this research was carried out, which aims to analyze the influence of social support and entrepreneurship education on interest in entrepreneurship. This research method uses a quantitative approach using multiple linear regression analysis. The population was taken from students of the undergraduate nutrition study program at University The results of this research show that the social support variable (X1) and the entrepreneurial education variable (X2) together have an influence on the entrepreneurial interest variable (Y) by 22.6%. Apart from that, it was also found that social support (X1) and entrepreneurship education (X2) separately also had a positive effect on interest in entrepreneurship (Y).